THE INFLUENCE OF PROBLEM BASED LEARNING ON THE STUDENTS’ WRITING SKILL IN HORTATORY EXPOSITION TEXT AT ELEVENTH GRADE OF SMA SAIDIYAH AROSBAYA - Lailatul Badriyah; Mariyatul Kiptiyah; Mohammad Kurdi Wijaya (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
Writing is one of the basic skills of the English language. It is usually considered one of the most difficulty skill than other skills of foreign language students. Even native speakers feel difficulty in showing good command of writing. In writing, the students need to acquire those first ideas to make sure what they want to write. They have to write about what they think in their mind and state it on paper by using the correct rules. In this research researcher use problem based learning method in teaching writing. The objective of this research to investigate the influence of problem based learning on the studnts’ writing skill in hortatory exposition text at eleventh grade of SMA Saidiyah Arosbaya. In conducting data, the researcher used quasi- experimental design. The population of this research was eleventh grade of SMA Saidiyah Arosbaya and sample were XI IPS 1 as experimental class and XI IPS 2 as control class. The result of this research based on the analysis data of Analysis of Covariance (ANCOVA) test from SPSS 17.0, the result of ANCOVA test from p-value was 0.035. It was less than the level of significant (0,05). If p-value<from the level of significant (0,05). It showed that the alternative hypothesis (Ha)was accepted and null hypothesis (Ho) was rejected.